Sosialisasi Sumber Energi Listrik Alternatif dari Buah-Buahan melalui Pengabdian Mengajar Santri di MIN 4 Kecamatan Peureulak Kabupaten Aceh Timur - Juwairiah, Juwairiah; Yurda Fitri; Muhammad Reza; Sandrina, Yayang Tri; Fajrina, Aila; Darliana, Fina; Khairunnisyah, Khairunnisyah; Salsabila, Nadia; Ramadayanti, Ramadayanti (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Socialization of alternative electrical energy sources from fruits through community service teaching students is a process of interaction and exchange of information between students of Madrasah Aliyah Swasta (MAS) Nurul Ulum, Peureulak, East Aceh and students of Madrasah Ibtidaiyah Negeri (MIN) 4 Peureulak, East Aceh. The purpose of the community service teaching program is that students of MAS Nurul Ulum can practice the knowledge they have acquired at MAS Nurul Ulum to be applied in the community through practical teaching activities. The community service teaching method uses the service-learning method. This activity has been carried out well, as can be seen from the positive response given by the students and the students' enthusiasm of Madrasah Ibtidaiyah Negeri (MIN) 4 in participating the socialization activity. The final results of the socialization activity showed an increase in the skills, knowledge, and insight of MIN 4 students regarding alternative electrical energy material. This program is also a means for students of MAS Nurul Ulum to increase their insight and experience. Through devotion to teaching students, it is also possible to establish good relations between MAS Nurul Ulum and MIN 4 Peureulak, East Aceh.